GAMES IN TEACHING SIMPLE PRESENT TENSE OF THE EIGHTH GRADE STUDENTS AT SMP NEGERI 7 AMPANA TETE - Nurhaida Lakuana; Jumrah Jumrah (English Education Study Program, 2021)
This research aims to find out whether students’ understanding in learning on simple present tense can be improved by using games or not. This research employed pre-experimental design. The variables of this research were games as the independent variable and the students’ understanding in learning simple present tense as the dependent variable. The population of this research was the VIII grade of SMP Negeri 7 Ampana Tete which consists of twenty five students. The technique sampling was total sampling, which means that all population was taken as the sample of this research. The researcher used test as the main instrument in this research which was divided into pre-test and post-test. The data analysis of this research used statistic calculation. The result of the research, the mean score of pre-test was 55.8 while the mean score in post-test was 87.2 and the testing hypothesis, the t-counted score was 11.80, while t-table for degree of freedom 24 and the level of significance = 0.05 was 1.710. It indicated that the hypothesis was accepted because games have improved students’ understanding in learning on simple present tense.